Philadelphia chromosome-negative classical myeloproliferative neoplasms: revised management recommendations from European LeukemiaNet - Barbui, Tiziano; Hehlmann, Rüdiger; Reiter, Andreas (Leukemia, 2018)
This document updates the recommendations on the management of Philadelphia chromosome-negative myeloproliferative neoplasms (Ph-neg MPNs) published in 2011 by the European LeukemiaNet (ELN) consortium. Recommendations were produced by multiple-step formalized procedures of group discussion. A critical appraisal of evidence by using Grades of Recommendation, Assessment, Development and Evaluation (GRADE) methodology was performed in the areas where at least one randomized clinical trial was published. Seven randomized controlled trials provided the evidence base; earlier phase trials also informed recommendation development. Key differences from the 2011 diagnostic recommendations included: lower threshold values for hemoglobin and hematocrit and bone marrow examination for diagnosis of polycythemia vera (PV), according to the revised WHO criteria; the search for complementary clonal markers, such as ASXL1, EZH2, IDH1/IDH2, and SRSF2 for the diagnosis of myelofibrosis (MF) in patients who test negative for JAK2V617, CALR or MPL driver mutations. Regarding key differences of therapy recommendations, both recombinant interferon alpha and the JAK1/JAK2 inhibitor ruxolitinib are recommended as second-line therapies for PV patients who are intolerant or have inadequate response to hydroxyurea. Ruxolitinib is recommended as first-line approach for MF-associated splenomegaly in patients with intermediate-2 or high-risk disease; in case of intermediate-1 disease, ruxolitinib is recommended in highly symptomatic splenomegaly. Allogeneic stem cell transplantation is recommended for transplant-eligible MF patients with high or intermediate-2 risk score. Allogeneic stem cell transplantation is also recommended for transplant-eligible MF patients with intermediate-1 risk score who present with either refractory, transfusion-dependent anemia, blasts in peripheral blood > 2%, adverse cytogenetics, or high-risk mutations. In these situations, the transplant procedure should be performed in a controlled setting.